Sensitization of supra-threshold pain responses—Translational aspects and mechanisms - Jonas, Robin; Schmelz, Martin (Frontiers in Network Physiology, 2022)
Despite spectacular advances in our understanding of molecular mechanisms of pain, remarkably little has changed with respect to available analgesic approaches for the treatment of pain, leaving a considerable proportion of chronic pain patients poorly treated. This discrepancy may be partially explained by a substantial translational gap in pain research, which is reflected by a mismatch of relevant primary pain assessment endpoints in preclinical vs. clinical trials. In this review, we consider the evidence for a need for supra-threshold pain assessment in the pain research literature. In addition to that, we focus on previous results that may demonstrate an example mechanism, where the detection of neuron-glial interactions on pain seems to be substantially depending on the assessment of pain intensity beyond threshold levels.